2013
DOI: 10.3855/jidc.2528
|View full text |Cite
|
Sign up to set email alerts
|

Availability and prescription practice of anti-malaria drugs in the private health sector in Yemen

Abstract: Introduction: Although the government of Yemen changed the national policy for treating malaria in November 2005 from chloroquine to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 17 publications
3
23
0
1
Order By: Relevance
“…However, this new policy was only implemented four years later in 2009 after proper training and distribution of the national guideline for antimalaria drugs were carried out (WHO, 2012). Despite these efforts, previous studies conducted in Hadhramout province reported that CQ is still commonly prescribed (18 out of 42 prescriptions) and some clinicians were not aware and had poor knowledge about the new national drug policy (Bashrahil et al, 2010;Ghouth, 2013). Continued use of CQ sustains the selection of CQ resistant mutations leading to persistence of mutant parasite.…”
Section: Introductionmentioning
confidence: 93%
“…However, this new policy was only implemented four years later in 2009 after proper training and distribution of the national guideline for antimalaria drugs were carried out (WHO, 2012). Despite these efforts, previous studies conducted in Hadhramout province reported that CQ is still commonly prescribed (18 out of 42 prescriptions) and some clinicians were not aware and had poor knowledge about the new national drug policy (Bashrahil et al, 2010;Ghouth, 2013). Continued use of CQ sustains the selection of CQ resistant mutations leading to persistence of mutant parasite.…”
Section: Introductionmentioning
confidence: 93%
“…Unfortunately, however, this policy was not implemented in practice until 2009. 16,17 Nevertheless, regardless of current antimalarial treatment guidelines, CQ remains the second most common antimalarial drug prescribed by physicians in public and private health facilities in Yemen. 16 As such, the results of this study should be utilised to educate health workers and medication manufacturers in Yemen as to the potential risk of CQ co-administration among khat-chewing patients.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Nevertheless, regardless of current antimalarial treatment guidelines, CQ remains the second most common antimalarial drug prescribed by physicians in public and private health facilities in Yemen. 16 As such, the results of this study should be utilised to educate health workers and medication manufacturers in Yemen as to the potential risk of CQ co-administration among khat-chewing patients. Current anti-malarial drug practices in Yemen should be modified accordingly and physicians should advise patients not to chew khat whilst undergoing CQ treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations